Adopting the Principles of Collagen Biomineralization for Intrafibrillar Infiltration of Yttria‐Stabilized Zirconia into Three‐Dimensional Collagen Scaffolds. (18th November 2013) - Zhou, Bin; Niu, Li‐na; Shi, Wei; Zhang, Wei; Arola, Dwayne D.; Breschi, Lorenzo; Mao, Jing; Chen, Ji‐hua; Pashley, David H.; Tay, Franklin R.
<x xml:space="preserve">Abstract</x> In this paper, a process for generating collagen‐yttria‐stabilized amorphous zirconia hybrid scaffolds by introducing acetylacetone‐inhibited zirconia precursor nanodroplets into a poly(allylamine)‐coated collagen matrix is reported. This polyelectrolyte coating triggers intrafibrillar condensation of the precursors into amorphous zirconia, which is subsequently transformed into yttria‐stabilized zirconia after calcination. These findings represent a new paradigm in the synthesis of non‐naturally occurring collagen‐based hybrid scaffolds under alcoholic mineralizing conditions.